konsep pendidikan multikulturan dan pendidikan inklusif - muhammad roihan alhaddad (Raudhah - Proud To Be Professional, 2020)
Education is one of the most decisive fields in the progress of a country. Indonesia is a unitary state consisting of various tribes, customs, religions, languages, and others. This unity will become a pluralistic form of the State through education. These differences can be united so that there is no corner discrimination in one of the groups so that Indonesia's development is delayed. In principle, multicultural education is education that respects differences. Multicultural education always creates structures and processes through which every culture can express. Of course, to design multicultural education in practice, it is not easy. But, at least we try to do ijtihad to design according to the principles of multicultural education. There are at least two things if we will realize multiculturalism education that is able to provide space for freedom for all cultures to express themselves.